MODERATING EFFECT OF FINANCIAL CAPABILITIES ON RELATIONSHIP BETWEEN INNOVATIVENESS AND GENERIC COMPETITIVE STRATEGY AMONG SMALL AND MEDIUM ENTERPRISES IN BAUCHI STATE, NIGERIA - Samaila, Dan’azumi; Inuwa, Umar; Ibrahim, Adamu (Kashere Journal of Management Sciences, 2024)
This study focused on moderating effect of financial capabilities on relationship between innovativeness and generic competitive strategy among small and medium enterprises in Bauchi state, Nigeria. The study adopted a survey research design which is purely quantitative, using structured questionnaire. The questionnaire was administered to 300 randomly selected owners/managers of small-scale businesses in Bauchi state. Data collected was analyzed using simple linear regression and hierarchical regression to test the hypotheses of the study. The findings of the study revealed that the relationship between innovativeness and generic competitive strategy among small and medium enterprises in Bauchi state, Nigeria was positive and significant. Equally, financial capabilities significantly moderated the relationship between innovativeness and generic competitive strategy among small and medium enterprises in Bauchi state, Nigeria. Therefore, the issues bedeviled SMEs in Bauchi state ranged from competition strategy, poor marketing skills, inadequate financial management, and low entrepreneurial spirit among others can be addressed through innovativeness and proper knowledge of how to manage finance and willingness to put that knowledge into practice. This study therefore, recommend that The Bauchi state government through the appropriate regulatory agency such as small and medium enterprises development agency of Nigeria (SMEDAN) should organize a seminars and workshop on regular basis to registered small-scale businesses operating in the state on how to come up with something new in terms of product, technology, marketing skills ahead of competitors and about the knowledge of how best to manage their money and willingness to put that knowledge into practice.